Attitude towards branded mobile applications and reuse intention : the moderating effect of gender and prior brand involvement - Rahul (2017)
Mobile applications (apps) have created a significant interest among advertisers and marketers, mostly because of their positive impact on user´s attitude and high level of engagement towards the brand. This study analyses the impact of gender-specific tendencies in the assessment of utilitarian and hedonic oriented branded mobile apps, highlighting that utilitarian content is favoured when intending to reuse mobile applications. The thesis strives to understand customer’s attitude towards branded mobile applications via pre-test and post-test survey focusing on four mobile branded applications- Google Map, Snapchat, Uber and Tinder. Pearson correlation and linear regression are used to understand the positive relationship between attitude and reuse intention and one-way Anova is used to understand gender preferences towards utilitarian and hedonic content of branded mobile apps. Results indicate that individual’s attitudes are strongly positively related with their reuse intention. Likewise, for Gender, men & women both have a higher tendency to reuse utilitarian apps, as contrary to the developed hypothesis that women mostly prefer hedonic app rather than utilitarian app. Additionally, the results conclude that the level of prior brand involvement may not necessarily moderate individual’s immediate response towards branded mobile application and reuse intention. Finally, implications associated with the findings are discussed with respect to clarifying possible outcomes obtained during result analysis and initiate solutions to improve further studies in this area.